Biochemical and Functional Characterization of GALT8, an Arabidopsis GT31 β-(1,3)-Galactosyltransferase That Influences Seedling Development - Narciso, Joan Oñate; Zeng, Wei; Ford, Kris; Lampugnani, Edwin R.; Humphries, John; Austarheim, Ingvild; van de Meene, Allison; Bacic, Antony; Doblin, Monika S. (Frontiers in Plant Science, 2021)
Arabinogalactan-proteins (AGPs) are members of the hydroxyproline-rich glycoprotein (HRGP) superfamily, a group of highly diverse proteoglycans that are present in the cell wall, plasma membrane as well as secretions of almost all plants, with important roles in many developmental processes. The role of GALT8 (At1g22015), a Glycosyltransferase-31 (GT31) family member of the Carbohydrate-Active Enzyme database (CAZy), was examined by biochemical characterization and phenotypic analysis of a galt8 mutant line. To characterise its catalytic function, GALT8 was heterologously expressed in tobacco leaves and its enzymatic activity tested. GALT8 was shown to be a β-(1,3)-galactosyltransferase (GalT) that catalyses the synthesis of a β-(1,3)-galactan, similar to the in vitro activity of KNS4/UPEX1 (At1g33430), a homologous GT31 member previously shown to have this activity. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) confirmed the products were of 2-6 degree of polymerisation (DP). Previous reporter studies showed that GALT8 is expressed in the central and synergid cells, from whence the micropylar endosperm originates after the fertilisation of the central cell of the ovule. Homozygous mutants have multiple seedling phenotypes including significantly shorter hypocotyls and smaller leaf area compared to wild type (WT) that are attributable to defects in female gametophyte and/or endosperm development. KNS4/UPEX1 was shown to partially complement the galt8 mutant phenotypes in genetic complementation assays suggesting a similar but not identical role compared to GALT8 in β-(1,3)-galactan biosynthesis. Taken together, these data add further evidence of the important roles GT31 β-(1,3)-GalTs play in elaborating type II AGs that decorate AGPs and pectins, thereby imparting functional consequences on plant growth and development.